Difluoromethylornithine attenuates isoproterenol-induced cardiac hypertrophy by regulating apoptosis, autophagy and the mitochondria-associated membranes pathway - Zhao, Yu (Exp Ther Med, 2021)
Myocardial hypertrophy is an independent risk factor of cardiovascular diseases and is closely associated with the incidence of heart failure. In the present study, we hypothesized that difluoromethylornithine (DFMO) could attenuate cardiac hypertrophy through mitochondria-associated membranes (MAM) and autophagy. Cardiac hypertrophy was induced in male rats by intravenous administration of isoproterenol (ISO; 5 mg/kg/day) for 1, 3,7 and 14 days. For DFMO treatment group, rats were given ISO (5 mg/kg/day) for 14 days and 2% DFMO in their water for 4 weeks. The expression of atrial natriuretic peptide (ANP) mRNA,heart parameters, apoptosis rate, fibrotic area and protein expressions of cleaved caspase3/9, GRP75, Mfn2, CypD and VDAC1 were measured to confirm the development of cardiac hypertrophy, apoptosis and autophagy induced by ISO. ANP mRNA and MAM protein expression levels were assessed by reverse transcription-quantitative PCR and western blotting to evaluate hypertrophy and the effects of DFMO oral administration. The results demonstrated that heart parameters, ANP mRNA levels, fibrotic area and apoptosis rate were significantly increased in the heart tissue for ISO 7 and 14 day groups compared with the control group. Furthermore, treatment with DFMO significantly inhibited these indicators, and DFMO downregulated the MAM signaling pathway and upregulated the autophagy pathway in heart tissue compared with the ISO 14 day group. Overall, all ISO-induced changes analyzed in the present study were attenuated following treatment with DFMO. The findings form this study suggested that DFMO treatment may be considered as a potential strategy for preventing ISO-induced cardiac hypertrophy.